LIMBAH DARI AKTIVITAS PENANGKAPAN IKAN DI PPN PALABUHANRATU - Deni A Soeboer; Fitri Irawan; Yopi Novita (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2020)
In the Ministry of Fisheries and Marine Affair Decree No. 45/2014 stated that an environmental consideration should take into account in controlling waste in fishing port area, including ship-generated waste. Marine pollution is one of the factors cause environmental damage including marine environment. Fishing activities is one of activites that has the potential to cause pollution of the sea. The objective of this research was to identify the waste type generated by fishing vessels and identify fishermens’s behavior patterns on the waste handling. The research was conducted in PPN Palabuhanratu (Palabuhanratu Nusantara Fishing Port). The data of waste type were collected from all kind of fishing vessels that grouped base on their dimension. The results show that, organic waste dominated the waste compotition, and from the fishers habit point of view most fishers still ignore the importance of marine pollution prevention effort. It showed from their habit to dispose waste not in the rigt place. Keywords: : fishing boats, marine pollution, organic waste, PPN Palabuhanratu